Effect of temperature and salinity on mortality of adults of Capitella sp. (Polychaeta: Capitellidae) under laboratory conditions. - Herrera-Perez, Melissa (2019)
Introduction: The marine-estuarine polychaete Capitella capitata is an endobenthic species which is considered as a cosmopolitan organism. The laboratory culture of this species-complex allows its use as a test species in toxicity bioassays and reproduction studies. Objective: It is pretended to observe mortality under two temperature and salinity ranges as optimal conditions to culture Capitella sp. in the laboratory. Metodology: Polychaetes were collected in Callao Province, Peru, during November 2016 and January 2017. A bioassay was carried out to observe mortality under different temperature and salinity ranges using two treatments: treatment 1, with polychaetes collected during January 2017, which were subjected to conditions similar to the collection site (temperature: 20-22° C, salinity: 30-32 psu); treatment 2, with the organisms collected during November 2016, with temperature (24-26 °C) and salinity (32 a 34 ups) selected according to bibliographic data. Results: The increase of temperature and time significantly influenced polychaete mortality of the two treatments (Spearman correlation), while salinity and dissolved oxygen did not show correlation with mortality. Significant effect of time was observed on mortality, with more deaths from the second half of the experiment. Organisms from treatment 1, with environmental conditions similar to those of their habitat survived more than worms from treatment 2. These results were also observed in the porcentual varibility of the variation coefficient among days in each treatment. The cumulative mortality curve did not show differences between treatments. Conclusion: The optimal ranges to culture Capitella sp. in the laboratory are those from their habitat. In addition to temperature and time, other posible causes of the observed mortality can be worms age, health or maturity, and probably the bad quality of the water used during the bioassay.